Anatomic predictor of severe prosthesis malposition following transcatheter aortic valve replacement with self- expandable Venus-A Valve among pure aortic regurgitation: A multicenter retrospective study - Wang, Yong; Yu, Shiyong; Qian, Dehui; Li, Jie; Fang, Zhenfei; Cheng, Wei; Li, Xiaoqing; Liu, Ting; Zeng, Ying; Xia, Hongmei; Jin, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Transcatheter aortic valve replacement (TAVR) in the treatment of patients with pure native aortic valve regurgitation (NAVR) has been based on the “off-label”indications, while the absence of aortic valve calcification and difficulty in anchoring was found to significantly increase the risk of prosthesis malposition. The aim of this study was to explore the anatomical predictors of severe prosthesis malposition following TAVR with the self-expandable Venus-A Valve among NAVR patients. Methods: A total of 62 NAVR patients who underwent TAVR with Venus-A Valve at 4 Chinese clinical centers were retrospectively observed. The clinical features, aortic MDCT data, and clinical outcomes were compared between non/mild malposition and severe malposition groups. Univariate logistic regression analysis was used to identify the risk factors of severe prosthesis malposition, and the receiver operating characteristic (ROC) curve was used to explore the predictive value of the risk factors. Results: Valve migration to ascending aortic direction occurred in 1 patient, and the remaining 61 patients (including 19 severe malposition cases and 42 non/mild malposition cases) were included in the analysis. The diameter and height of sinotubular junction (STJ), and STJ cover index (STJCI, calculated as 100%*STJ diameter/nominal prosthesis crown diameter) were all greater in severe malposition group (all p<0.05). Logistic regression showed that STJ diameter (OR=1.23, 95%CI 1.04-1.47, p=0.017), STJ height (OR=1.24, 95%CI 1.04-1.47, p=0.017) and STJCI (OR=1.08, 95%CI 1.01-1.16, P=0.032) were potential predictors for severe prosthesis malposition. The area under the ROC curve was 0.72 (95% CI 0.58-0.85, p=0.008) for STJ diameter, 0.70 (95% CI 0.55-0.86, p=0.012) for STJ height and 0.69 (95% CI 0.55-0.83, p=0.017) for STJCI, respectively. The cutoff value for STJ diameter was 33.2 mm (sensitivity was 84.2% and specificity was 65.8%), and that was 24.1mm for STJ height (sensitivity was 57.9% and specificity was 87.8%) and 81.0% for STJCI (sensitivity was 68.4% and specificity was 68.3%), respectively. Conclusions: Larger and higher STJ as well as greater STJ to valve crown diameter ratio may help identify patients at high risk for severe prosthesis malposition among NAVR patients undergoing TAVR with Venus-A prosthesis valve.